KEANEKARAGAMAN JENIS REPTIL DI CAGAR ALAM RAYA PASI GUNUNG POTENG KOTA SINGKAWANG PROVINSI KALIMANTAN BARAT - Bari, Zunaidi; Nurdjali, Bachrun; Nugroho, Joko (JURNAL HUTAN LESTARI, 2018)
Reptile is one of the group of Â herpetofauna. The purpose of this study was to determine the Reptile Species Diversity in Nature Reserves Raya Pasi Singkawang. The method Visual Encounter Survey (VES). List of species of reptiles found in kawasan Cagar Alam Kingdom Pasi Gunung 22 kinds of 6 famyli. Based on the results of measurements obtained during field range of temperatures 260C-280C, 220C-240C water temperature, air humidity between 770C-780C. Analysis of the data showed species diversity index (H ') is highest in tersterial habitat value H' = 1,059 and the lowest in aquatic habitats with the value H '= 0.7674. While the evenne==ss index (e) is highest in tersrerial habitat with a value of e = 0.828 and lowest in aquatic habitats with a value of e = 0.804. As for the similarity index value type (S) between the two habitats is obtained with a value of 0.4 which means approximately 40% in both types of Reptiles Order Squamata these habitats are the same and 60% of Reptiles Order Squamata are not the same in both habitats. The chance encounter owned by eutropis rudis types of 0.347222 individuals / hour.Keyword: Diversity, Mount Poteng, Reptile, Singkawang